Diasporic Female Identity in the Select Novels of Bharati Mukherjee - Mohan Bain, Maitry (International Journal of Psychosocial Rehabilitation, 2019)
Bharati Mukherjee as a Diasporic writer has given a new direction to Indian writing in English. So as a Diasporic writer she expresses her personal experience as a woman immigrant. She has played a significant role in typical Indian feelings of women and feelings of immigrants through her writings. Quest for self-identity is the basic concern of her female protagonist. This paper mainly focuses on two novels, The Tiger’s Daughter and Jasmine by Bharati Mukherjee. She highlights the condition of Asian immigrants in North America and Canada they are searching for their identity in an alien land. Bharati Mukherjee herself has experienced the agony of nostalgia and solitude which are express in her writings. Bharati Mukherjee highlights the concept of identity, nostalgia, deconstruction of self, adjustment, disappointment of expatriation, cultural transformation, dislocation, and negotiation. So, these are the issues that are present in her novels. It examines the feelings of isolation rootlessness and alienation. The works of Bharati Mukherjee focuses on the thematic analysis with special attention on cultural transplant which leads to an identity crisis. She defines women identity within the parameters of social structure. Bharati Mukherjee tries to study the phenomenon of immigration, the status of new immigrants, the feeling of rootlessness and alienation, experienced by her women characters in The Tiger’s Daughter and Jasmine.